DAYA SAING SUMBER DAYA MANUSIA DI ERA DIGITALISASI - Kurniawan, Zuki (Jurnal EBI, 2023)
The era of digitalization has fundamentally changed the landscape of work and business. In this context, the competitiveness of human resources is the key to facing the challenges and opportunities offered by the digital revolution. This article describes the role and main factors that influence the competitiveness of human resources in the era of digitalization. Education and training in digital skills, adaptability, communication skills, innovation, and understanding of cyber security are key elements in preparing the workforce for success in an increasingly connected and digitalized environment. In addition, the importance of awareness of digital ethics and policies as well as the role of government in creating an environment that supports technological development was also discussed. In conclusion, to achieve high competitiveness in the digital era, collaboration between individuals, organizations and governments in the development and maintenance of relevant skills becomes very important.Keyword: human resources